AB0230 Symptoms of Depression, Anxiety and Poor Sleep Quality in Patients Followed in a Rheumatology Day-Care Unit: Associated Sociodemographic and Disease-Related Factors. (9th June 2015) - Raposo, A.; Lopes, E.; Sousa Neves, J.; Cerqueira, M.; Teixeira, F.; Costa, J.; Pina, P.; Afonso, C.
Abstract : Background: The presence of depression, anxiety and sleep disorders are common among patients with inflammatory rheumatic diseases. Frequently are underdiagnosed in clinical practice and can negatively influence the perception of pain by the patient, the disease activity and the individual's quality of life. Objectives: To determine the levels of depression, anxiety and sleep quality in patients with inflammatory rheumatic diseases followed in a rheumatology day-care unit, with current or past history of biological treatment, and to identify associated demographic and disease-related factors. Methods: The Beck depression and anxiety inventory (BDI and BAI) and Pittsburgh sleep quality index (PSQI) were applied as instruments for measuring the severity of depression, anxiety and sleep quality, respectively. Disease activity was ascertained using validated clinical index: ASDAS-PCR for spondylarthritis with predominant axial involvement and DAS28-ESR for spondylarthritis with predominant peripheral involvement or rheumatoid arthritis. Health Assessment Questionnaire (HAQ) was used to assess impairment in daily activities due to illness and Short Form-36 (SF-36) to assess health related quality of life. A p value of <0.05 was considered as significant. Results: A total of 84 patients were consecutively included, of which 50 (59.5%) were female, with a mean age of 46.25±13.25 years (19 to 85) and a mean disease duration of 14.62±8.07 years (1 to 38). Thirty six (42.9%) patients had rheumatoid arthritis and 48 (57.1%) had spondylarthritis. Symptoms of anxiety and depression were found in 46 (54.8%) and 30 (35.7%) patients, with moderate or severe score in 23 (27.3%) and 14 (16.7%) patients respectively. Thirteen (15.5%) patients were taking antidepressant treatment. Poor sleep quality was found in 53 (63.1%) patients but only 14 (16.7%) took sleeping pills. Strong correlation ( p <0.01) was found between high scores of anxiety, depression and sleep index. These scores correlated too with high HAQ and pain on a VAS, low SF36 and both on their mental and emotional components ( p <0.01). High ASDAS-PCR scores were positively correlated with anxiety, depression and sleep index ( p <0.01). Similarly high DAS-28 positively correlated with depression ( p <0.01) and poor sleep quality ( p <0.05), but not with anxiety. The female gender and other than single civil status were associated with higher anxiety and history of hypertension with more depressive symptoms ( p <0.05). Active employees and current corticosteroid treatment were associated both with higher anxiety and depression scores ( p <0.05). Older age and longer disease duration associated with poorer sleep quality ( p <0.05). The scores were not statistically different between bDMARDS or cDMARDS, the kind of disease, habits or other associated diseases. Conclusions: Anxiety, depression and sleep disorders were very prevalent in this patient group. Higher disease activity, worse quality of life and higher pain were noted in the presence of these disturbances. The female gender, civil status, employment, corticoid therapy and history of hypertension were also associated. Recognize and treat both conditions is important to best manage these patients. Disclosure of Interest: None declared